Credit Risk Management and profitability of Commercial Banks in Nepal - Chaudhary, Shiva Chandra (Medha: A Multidisciplinary Journal, 2025)
Credit risk management is an important aspect for a banking institution. This study attempted to investigate the relationship between credit risk management and profitability of commercial bank in Nepal. To examine its relationship the researcher uses ratio analysis and Karl Pearson's coefficient of correlation and also test its significance by taking 5 years ROA and ROE as dependent variables and non-performing assets(NPAs) and Capital Adequacy Ratio(CAR) as independent variables from each bank. The study also suggest that the bank should manage their credit risk well by interpreting customer historical data before providing loans and advance to the borrowers. Data was analyzed by using descriptive analysis, ratio analysis.co-relation.